PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS E- MODUL INTERAKTIF MENGGUNAKAN APLIKASI CANVA UNTUK MENINGKATKAN LITERASI SAINS PADA SISWA SEKOLAH DASAR - Fitri, Nur Choiriah; Roesminingsih, Erny; Widiasih, Widiasih (Universitas Negeri Makassar, 2024)
This development research is motivated by the presentation of science material in grade 6 thematic books that are incoherent and lack depth which has an impact on students' lack of interest in reading even though the learning outcomes have not reached the minimum completeness criteria. This research includes development research with the Four-D model consisting of the stages of defining, designing, developing, and disseminating carried out in schools. The subjects of this study were grade 6B students totaling 37 students at SDN Made I / 475 Surabaya. Researchers have carried out media validation of interactive e-modules that are developed and considered suitable for use. Analysis of the implementation stage showed that the percentage of the validity rate of interactive e-module media reached 97.6% and the percentage of media practicality reached 94.87%, both of which showed very good criteria. The effectiveness of student learning outcomes has exceeded the minimum completeness criterion by 85.8 and increased student success by 39.3%. Analysis of literacy test results showed that science literacy increased from level 4 to level 5 with an N-gain of 0.67 in the moderate category. Researchers concluded that interactive e-modules using the developed Canva application are valid and practical to use, and effective for improving science literacy.